Vocational education and training (VET) for youths with low levels of qualification in Germany - Schmidt, Christian [Verfasser] (My University, 2010)
"In Germany structural change and aggravated international competition have been accompanied by a declining willingness of enterprises to offer apprenticeships. Young people with low levels of qualification increasingly end up in courses at vocational schools that offer few transitions to regular VET or the labour market. This paper aims to show how the German VET (vocational education and training) system turned from an inclusive scheme to a selective scheme regarding young people with low levels of qualifications from basic schooling. The paper presents empirical results of an evaluation study on the background of the structural changes in German VET." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 2.3.5 Wirtschaftsstrukturwandel; G 1.3.2.2 Übergänge; P 1.1 Jugendliche; P 1.7 Benachteiligte; Berufsbildungssystem; Duales System; Reform; Wirtschaftsstrukturwandel; Berufseinmündung; Übergangssystem; Benachteiligter Jugendlicher